(untitled) (Academia Journal of Medicine, 2026)
Periodontitis is a multifactorial chronic inflammatory disease characterized by complex interactions among microbial dysbiosis, host immune response, genetic predisposition, environmental factors, and systemic conditions. Conventional periodontal therapy largely follows a standardized approach despite substantial inter-individual variation in disease susceptibility, progression, and treatment response. Precision periodontics has emerged as a paradigm shift that integrates genomic, proteomic, metabolomic, microbiomic, biomarker, clinical, and digital data to tailor preventive and therapeutic interventions for individual patients. Recent advances in salivary diagnostics, artificial intelligence (AI), multi-omics technologies, and personalized regenerative therapies are enabling risk prediction, early diagnosis, and customized treatment planning. This review discusses the biological basis, diagnostic tools, therapeutic applications, current challenges, and future directions of precision and personalized periodontics.